1998
DOI: 10.1063/1.122843
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence measurements of InGaN light-emitting diodes

Abstract: Radiative and nonradiative recombination processes in ultraviolet light-emitting diode composed of an In 0.02 Ga 0.98 N active layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 24 publications
4
54
1
Order By: Relevance
“…The excitation density dependence results from band filling effects, both in k-space resulting in recombination on the high-energy side of the spectrum. The recombination dynamics can be interpreted by the model of Pophristic et al [11] which accounts for strongly localized disordered systems and was found to be descriptive for the hexagonal GaInN system. By applying this model to our measurements we found a good agreement with the predictions.…”
Section: Discussionmentioning
confidence: 98%
“…The excitation density dependence results from band filling effects, both in k-space resulting in recombination on the high-energy side of the spectrum. The recombination dynamics can be interpreted by the model of Pophristic et al [11] which accounts for strongly localized disordered systems and was found to be descriptive for the hexagonal GaInN system. By applying this model to our measurements we found a good agreement with the predictions.…”
Section: Discussionmentioning
confidence: 98%
“…Patterned sapphire substrates (PSSs) 23 or roughening in vertical LEDs (VLEDs) achieve light extraction efficiencies of over 80% today. 24,25 Methods are still under investigation to reduce TIR by surface roughening, 26 substrate patterning, chip shape optimization, and material integrating/embedding. 2 The internal quantum efficiency (IQE), the ratio of generated photons to the electron-hole recombination, was increased by improving the material quality and modification to to LED device structures.…”
Section: The Iii-nitrides For Light-emitting Diodesmentioning
confidence: 99%
“…Pophristic et al [23,24] discussed the timeresolved PL of InGaN light-emitting diodes and multiple quantum wells. They report a value of b increasing from 0.75 to 0.85 with increasing indium phase segregation, and emphasize that the stretched-exponential kinetics is consistent with the presence of disorder.…”
Section: Introductionmentioning
confidence: 99%